P12 LONG-TERM QUALITY OF LIFE AFTER TOTAL GASTRECTOMY VERSUS IVOR LEWIS ESOPHAGECTOMY. (23rd November 2019) - Jezerskyte, E; Saadeh, L M; Hagens, E R C; Sprangers, M A G; Noteboom, L; van Laarhoven, H W M; Eshuis, W J; van Berge Henegouwen, M I; Gisbertz, S S
Abstract: Aim: The aim of this study was to investigate the difference in long-term health-related quality of life in patients undergoing total gastrectomy versus Ivor Lewis esophagectomy in a tertiary referral center. Background & Methods: Surgical treatment for gastroesophageal junction (GEJ) cancers is challenging. Both a total gastrectomy and an esophagectomy can be performed. Which of the two should be preferred is unknown given the scarce evidence regarding effects on surgical morbidity, pathology, long-term survival and health-related quality of life (HR-QoL). From 2014 to 2018, patients with a follow-up of > 1 year after either a total gastrectomy or an Ivor Lewis esophagectomy for GEJ or cardia carcinoma completed the EORTC QLQ-C30 and EORTC QLQ-OG25 questionnaires. Problems with eating, reflux and nausea and vomiting were chosen as the primary HR-QoL endpoints. The secondary endpoints were the remaining HR-QoL domains, postoperative complications and pathology results. Multivariable linear regression was applied taking confounders age, gender, ASA classification and neoadjuvant therapy into account. Results: 30 patients after gastrectomy and 71 after Ivor Lewis esophagectomy with a mean age of 63 years were included. Median follow-up was two years (range 12-84 months). Patients after total gastrectomy reported significantly less choking when swallowing and coughing (β=-5.952, 95% CI -9.437 – -2.466; β=-13.084, 95% CI -18.525 – -7.643). Problems with eating, reflux and nausea and vomiting were not significantly different between the two groups. No significant difference was found in postoperative complications or Clavien-Dindo grade. Significantly more lymph nodes were resected in esophagectomy group (p=0.008). No difference in number of positive lymph nodes or R0 resection was found. Conclusion: After a follow-up of > 1 year choking when swallowing and coughing were less common after total gastrectomy. No significant difference was found in problems with eating, reflux or nausea and vomiting nor in postoperative complications or radicality of surgery. Based on this study no general preference can be given to either of the procedures for GEJ cancer. Patients may be informed about the HR-QoL domains that are likely to be affected by the different surgical procedures, which in turn may support shared decision making when a choice between the two treatment options is possible.